Helicobacter Species as Possible Risk Factor in Gallbladder Cancer and Gallstones: A Meta-Analysis - Trixie, Joue Abraham; Hartman, Kirsten Putriani; Esterini, Dwita Nitoya; Dias, Dany; Lele, Juan Alessandro Jeremis Maruli Nura (The Indonesian Society for Digestive Endoscopy, 2022)
Background: It has been long known that Helicobacter species are one of the leading causes in gastrointestinal diseases. Recently, it is emerging as one of the causes leading to gallbladder diseases, such as gallbladder cancer and gallstones. The aim of this study is to assess the correlation between Helicobacter species and gallbladder cancer and gallstones.Method: This meta-analysis assessed case-control studies from the year 2001 to 2022. A comprehensive literature search was performed in Pubmed, Scopus, Embase, dan Plos One. Review manager 5.4.1, along with the Mantel Haenszel method, was utilized to analyze the data extraction. The methodological index was utilized to assess the risk of bias from the included studies. The odds ratio is calculated with a confidence interval of 95%. P 0.05 was considered significant.Results: Twenty case-control studies from the year 2001 to 2018 with a total number of 2,065 participants were included. We found that there is a low risk of bias and a significant difference between the control group and the experimental group; gallbladder cancer (random effect: OR = 2.38; 95% CI: 1.35–4.19; p = 0.003) and gallstones (fixed effect: OR = 4.17; 95% CI: 2.71– 4.62; p = 0.00001).Conclusion: Results of this meta-analysis demonstrated that the patients with Helicobacter species have an increased risk of gallbladder cancer and gallstones.